2019
DOI: 10.1108/jd-06-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Metadata categorization for identifying search patterns in a digital library

Abstract: For digital libraries, it is useful to understand how users search in a collection. Investigating search patterns can help them to improve the user interface, collection management and search algorithms. However, search patterns may vary widely in different parts of a collection. This study demonstrates how to identify these search patterns within a well-curated historical newspaper collection using the existing metadata. Design/methodology/approach: The authors analyzed search logs combined with metadata reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Log analysis in digital libraries Search logs collected from digital libraries and archives has been studied frequently [2,3,6,10,12,15,16,19]. In some cases, studies focus on the detection and analysis of (topical) user interests, for example to categorize search topics [10,15], or to identify usage patterns in different parts of the collection [2,3]. These studies focus on a statistical analysis of search logs.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Log analysis in digital libraries Search logs collected from digital libraries and archives has been studied frequently [2,3,6,10,12,15,16,19]. In some cases, studies focus on the detection and analysis of (topical) user interests, for example to categorize search topics [10,15], or to identify usage patterns in different parts of the collection [2,3]. These studies focus on a statistical analysis of search logs.…”
Section: Related Workmentioning
confidence: 99%
“…Documents in a digital library are frequently described using bibliographic metadata. Clicked documents can be annotated with this metadata, providing insights into the parts of the collection the user searched [3]. format is uncomplicated, providing an overview of user queries and clicked results.…”
Section: Session Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A digital library is a collection of information that is both digitized and organized (Lesk, 2005) and can be searched for different patterns (Bansode and Shinde, 2019; Bogaard et al , 2019). Over the years, there has been a growing body of multilingual digital libraries (Diekema, 2012; Wu and Chen, 2019) that store content in more than one language.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the work presented in [34] demonstrated different search patterns of users searching for five major religions. In a previous study, we observed a distinct search pattern for users searching for documents related to World War II (WWII) [5]. For these types of studies, we need to be able to retrieve those user interactions from the search logs that relate to a user interest in a specified topic.…”
Section: Introductionmentioning
confidence: 99%